Design Analysis of Permanent Magnet Synchronous Generator (Pmsg) 18 Slot 8 Pole to Seek Efficiency in Series and Parallel Circuits - Veronica Ernita Kristianti; Priska Restu Utami; Aris Susanto (PT FORMOSA CENDEKIA GLOBAL, 2023)
Generator is an important component for converting renewable energy into electrical energy. This study aims to analyze the efficiency of designing a Permanent Magnet Synchronous Generator (PMSG) with a configuration of 18 slots 8 poles in series and parallel circuits. The research was conducted by simulating using Infolytica MagNet software and data analysis using Microsoft Excel. The test results show that the design efficiency of the PMSG generator is higher in a series circuit up to 84% at a speed of 2000 RPM and a load of 20 W compared to a parallel circuit which is only 13% at a speed of 3000 RPM and a load of 10 W.. PMSG generator design, series configuration is more efficient than parallel configuration. The results of the study show that the performance and efficiency of the 18 slot 8 pole PMSG generator can be used for renewable energy based power generation systems.